Controllable wavelength channels for Multiwavelength Brillouin Bismuth/Erbium based fiber Laser - Ahmad, Harith; Zulkifli, Mohd Zamani; Norizan, Siti Fatimah; Latif, Amirah Abdul; Harun, Sulaiman Wadi (Electromagnetics Academy, 2009)
We propose and demonstrate a Multiwavelength Brillouin Bismuth/Erbium Fibre Laser (MBBEFL) with the ability to control the number of wavelength channels generated. A multi-wavelength comb output is obtained using a 7.7km DCF as a non linear gain medium to generate Stokes wavelengths through the process of Stimulated Brillouin Scattering (SBS). The DCF is pumped by a Raman pump source at 400mW to lower the dispersion loss and promote the generation of the Stokes wavelengths. A 49cm long Bismuth based Erbium Doped Fibre (Bi-EDF) is used as an optical amplifier to provide the necessary gain for the Brillouin Pump and also act as the gain medium for the generated Stokes signal.